Struktur Kepribadian Tokoh dalam Novel Melangkah Karya J.S. Khairen - Jannah, Nur; Muliatik, Sri; Wulandari, Wina (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
This study analyzes the character values and personality dynamics of the main characters in J.S. Khairen's novel Melangkah through Sigmund Freud's psychoanalytic approach, specifically the id, ego, and superego structures. A descriptive qualitative research method with content analysis was applied to examine text excerpts representing the behavior, dialogue, and internal conflicts of the characters, namely Runa, Aura, Siti, Arif, and Ocha. The research findings indicate that each character undergoes unique personality development, influenced by the interplay between instinctual drives (id), rational considerations (ego), and moral consciousness (superego). For example, Runa illustrates a transition from impulsivity (id) to self-control (superego), while Siti and Ocha are more dominated by the ego, emphasizing realistic adaptation. Character values such as perseverance, courage, and politeness are identified as key elements that shape the characters' identities while driving the plot. This study contributes theoretically to literary psychology research and practically to the development of multidimensional fictional character writing. Implicitly, these findings can serve as a reference for educators in utilizing literature as a medium for contextual character education.